2017
DOI: 10.3389/fmicb.2017.01192
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Causes Endoplasmic Reticulum Stress and Induces the Unfolded Protein Response in Saccharomyces cerevisiae

Abstract: Since acetic acid inhibits the growth and fermentation ability of Saccharomyces cerevisiae, it is one of the practical hindrances to the efficient production of bioethanol from a lignocellulosic biomass. Although extensive information is available on yeast response to acetic acid stress, the involvement of endoplasmic reticulum (ER) and unfolded protein response (UPR) has not been addressed. We herein demonstrated that acetic acid causes ER stress and induces the UPR. The accumulation of misfolded proteins in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 64 publications
2
37
1
Order By: Relevance
“…We examined two conditions for each stress (except for glucose starvation), namely, mild stress condition and severe stress condition. The mild stress conditions (0.1% acetic acid, 8% ethanol, heat shock at 37°C, and 0.4 m m H 2 O 2 ) activate various stress‐responsive transcriptional factors and inhibit yeast growth, whereas the severe stress conditions (0.2% acetic acid, 10% ethanol, heat shock at 42°C and 1.0 m m H 2 O 2 ) cause serious effects on yeast including cell death (Figley, Bieri, Kolaitis, et al, ; Izawa, Kita, Ikeda, et al, ; Kawazoe, Kimata, & Izawa, ; Mariani, Mathias, da Silva, et al, ; Narendranath, Thomas, & Ingledew, ; Nguyen et al, ; Yamamoto & Izawa, ; Yamauchi & Izawa, ). It has been reported that heat shock activates the transcription of YLL056C (Wu & Li, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined two conditions for each stress (except for glucose starvation), namely, mild stress condition and severe stress condition. The mild stress conditions (0.1% acetic acid, 8% ethanol, heat shock at 37°C, and 0.4 m m H 2 O 2 ) activate various stress‐responsive transcriptional factors and inhibit yeast growth, whereas the severe stress conditions (0.2% acetic acid, 10% ethanol, heat shock at 42°C and 1.0 m m H 2 O 2 ) cause serious effects on yeast including cell death (Figley, Bieri, Kolaitis, et al, ; Izawa, Kita, Ikeda, et al, ; Kawazoe, Kimata, & Izawa, ; Mariani, Mathias, da Silva, et al, ; Narendranath, Thomas, & Ingledew, ; Nguyen et al, ; Yamamoto & Izawa, ; Yamauchi & Izawa, ). It has been reported that heat shock activates the transcription of YLL056C (Wu & Li, ).…”
Section: Resultsmentioning
confidence: 99%
“…serious effects on yeast including cell death (Figley, Bieri, Kolaitis, et al, 2014;Izawa, Kita, Ikeda, et al, 2008;Kawazoe, Kimata, & Izawa, 2017;Mariani, Mathias, da Silva, et al, 2008;Narendranath, Thomas, & Ingledew, 2001;Nguyen et al, 2014;Yamauchi & Izawa, 2016). It has been reported that heat shock activates the transcription of YLL056C (Wu & Li, 2008).…”
Section: Furfural and Hmf Induced The Protein Synthesis Of Yll056cmentioning
confidence: 99%
“…Many factors contribute to protein unfolding and misfolding. These include overexpression of an exogenous protein, e.g., a mouse protein in yeast cells [76], disruption of O-mannosylation in yeast [77], imbalance of ion concentrations such as calcium [78] and cadmium [79], excess of acetic acid, propionic acid and sorbic acid [80], antifungal agents that perturb protein folding such as monoterpene carvacrol [81,82], tunicamycin [18], dithiothreitol [83,84,85], hypoxia [86], or acidosis [67].…”
Section: How Is Ire1p Activity Regulated In Response To Unfolded/mmentioning
confidence: 99%
“…Miyagawa et al (2014) reported that culturing cells under high-ethanol conditions causes protein denaturation and aggregation, which activate Ire1. Moreover, acetic acid, a byproduct of bioethanol production from lignocellulosic biomass, is reported to be an ER stressor (Kawazoe et al 2017). The environmental pollutant cadmium also activates Ire1 through impairment of protein folding in S. cerevisae ER (Le et al 2016).…”
Section: Conditions In Which the Upr Functions In S Cerevisiae Cellsmentioning
confidence: 99%